Effectiveness and safety of apixaban vs warfarin among older venous thromboembolism patients: a subgroup analysis of age. (14th October 2021) - Cohen, A; Sah, J; Dhamane, A; Lee, T; Rosenblatt, L; Hlavacek, P; Emir, B; Keshishian, A; Yuce, H; Luo, X
Abstract: Background: Venous thromboembolism (VTE) is the third most common cardiovascular condition in adult patients. Older patients are at an increased risk of VTE. However, they have been underrepresented in clinical trials and evidence on the safety and effectiveness of anticoagulants in older VTE patients, especially very elderly patients (≥80 years), is sparse. Purpose: To evaluate the risk of recurrent VTE, major bleeding (MB), and clinically relevant non-major (CRNM) bleeding among older VTE patients initiating apixaban or warfarin according to two age sub-groups: 65–79 and ≥80 years. Methods: Older VTE patients (aged ≥65 years) who initiated apixaban or warfarin were identified from the CMS Medicare database (September 2014–December 2017). To balance the characteristics between apixaban and warfarin patients, stabilized inverse probability treatment weighting (IPTW) was conducted. Post IPTW, a subgroup interaction analysis was conducted to evaluate if there was any difference in treatment effects between the two age subgroups (65–79 vs. ≥80) on recurrent VTE, MB, and CRNM bleeding. Cox proportional hazard models were used to conduct the interaction analysis, and the statistical significance of the interaction was set to p-value <0.10. Results: A total of 22, 135 apixaban and 45, 840 warfarin patients with VTE aged ≥65 years were eligible for analysis. Post IPTW, patient characteristics were balanced between the apixaban and warfarin treatment cohorts. Apixaban patients had significantly lower risk of recurrent VTE, MB, and CRNM bleeding compared to warfarin patients (Figure). 42, 551 (62.6%) were aged 65–79 years and 25, 424 (37.4%) were aged ≥80 years. Among apixaban or warfarin patients, those aged 65–79 years had lower Charlson comorbidity index scores (mean 2.7 vs 3.2) and were less likely to have a diagnosis of anemia (34.7–34.9% vs 42.3–42.5%), cerebrovascular disease (14.7–15.7% vs 20.3–20.5%), or dementia (5.0–6.9% vs 20.4–24.6%) compared to patients aged ≥80 years. Across both age subgroups, incidence rates of recurrent VTE, MB and CRNM bleeding were lower for apixaban vs. warfarin. No significant interaction was observed between the treatment and age on recurrent VTE and MB (Figure). There was a significant interaction between treatment and age on CRNM bleeding. Apixaban trended towards a lower risk of CRNM bleeding across both age groups but the treatment effect on CRNM bleeding was larger for patients aged 65–79 years. Conclusion: The treatment effects of apixaban vs. warfarin on recurrent VTE and MB were consistently observed across both older age groups in this analysis. More studies are needed to evaluate management of VTE in an older and especially the very elderly population. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Bristol-Myers Squibb Company and Pfizer Inc.